2020
DOI: 10.2147/dddt.s256756
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel HDAC/Tubulin Dual Inhibitor: Design, Synthesis and Docking Studies of α-Phthalimido-Chalcone Hybrids as Potential Anticancer Agents with Apoptosis-Inducing Activity</p>

Abstract: Introduction: In order to develop novel anticancer HDAC/tubulin dual inhibitors, a novel series of α-phthalimido-substituted chalcones-based hybrids was synthesized and characterized by IR, 1 H NMR, 13 C NMR, mass spectroscopy and X-ray analysis. Methods: All the synthesized compounds were evaluated for their in vitro anticancer activity against MCF-7 and HepG2 human cancer cell lines using MTT assay. To explore the mechanism of action of the synthesized compounds, in vitro β-tubulin polymerization and HDAC 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Chalcones have been shown to exhibit anticancer activity through their inhibitory potential against various targets, such as 5α-reductase [ 187 ], aromatase [ 188 ], histone deacetylase inhibitors (HDAC) [ 189 , 190 ], proteasome [ 191 , 192 ], JAK/STAT signaling pathways [ 193 ], cell division cycle 25 (CD25) [ 194 ], cathepsin-K [ 72 , 195 ], topoisomerase-II [ 196 , 197 ], Wnt [ 198 , 199 ], ROS/MAPK [ 200 ], p38 [ 201 , 202 ] and mTOR [ 203 , 204 ]. However, these studies are not covered in this review because not enough evidence has been provided to indicate that these proteins or pathways are direct targets of chalcones.…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…Chalcones have been shown to exhibit anticancer activity through their inhibitory potential against various targets, such as 5α-reductase [ 187 ], aromatase [ 188 ], histone deacetylase inhibitors (HDAC) [ 189 , 190 ], proteasome [ 191 , 192 ], JAK/STAT signaling pathways [ 193 ], cell division cycle 25 (CD25) [ 194 ], cathepsin-K [ 72 , 195 ], topoisomerase-II [ 196 , 197 ], Wnt [ 198 , 199 ], ROS/MAPK [ 200 ], p38 [ 201 , 202 ] and mTOR [ 203 , 204 ]. However, these studies are not covered in this review because not enough evidence has been provided to indicate that these proteins or pathways are direct targets of chalcones.…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…It has been reported that the combination of SAHA and vincristine (a tubulin inhibitor) could achieve synergistic effects in leukemia, which provides a theoretical basis for designing dual tubulin/HDAC inhibitors. Several groups have reported the discovery of novel tubulin/HDAC dual inhibitors in recent years. , For instance, Diana and co-workers designed dual tubulin/HDAC inhibitors that demonstrated potent anticancer activities . Despite these advancements, the therapeutic value of dual tubulin/HADC inhibitors (in particular, dual inhibitors with HDAC-isoform-selectivity) remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…The results of PLIP analysis of training set compounds and simulated hits showed a concrete relationship between the salient chemical features (Hypo 1) present in training set compounds (FDA approved drugs) and molecular interactions observed in simulated hits in complex with HDAC3. The structural information for five drug molecules such as TSA (5EEF, 16), LBH (5EF8, 1), JNJ-26481585 (6HSK, 2), ACY-1215 (5WGL, 1), and SHH (4LXZ, 11) was retrieved from the crystal structures whereas, for NVP-LAQ824, MS-275 and VPA drugs were obtained from the earlier docking studies 58 60 . Total 31 co-crystal structures of these five drugs were downloaded from the protein data bank and analyzed for protein–ligand interactions profiles using PLIP online server and DS.…”
Section: Resultsmentioning
confidence: 99%